ZnO-Zn composite porous block for negative electrode of zinc-nickel battery and preparation method of ZnO-Zn composite porous block
The preparation of ZnO-Zn composite porous block negative electrode material by sol-gel accompanying phase separation method solves the problem of poor circulation performance of zinc-nickel negative electrodes, achieves higher cycle stability and conductivity, and improves the overall performance of the battery and Security.
Patent Information
- Application Number
- CN202310987757.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
AI Technical Summary
The cycling performance of the negative electrode of the zinc nickel battery is restricted by the problem of zinc dendrites, resulting in a decrease in capacity and damage to the diaphragm, which in turn affects the safety and stability of the battery and energy storage efficiency.
The zinc hydroxide porous block is prepared by sol-gel accompanying phase separation method, and the ZnO-Zn composite porous block negative electrode material is formed by heat treatment, so as to control the mass ratio of ZnO and Zn between 10:1 and 5:1 to form porous Structure to inhibit dendrite growth and improve conductivity through organic carbonization.
It effectively alleviates the growth of Zn dendrites, improves the circulation and conductivity of the negative electrode, extends the service life of the battery, and improves the electrochemical performance and safety and stability.
Smart Images

Figure CN119430268A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc-nickel batteries, and in particular relates to a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery and a preparation method thereof. Background Art
[0002] Wind and solar power generation has the disadvantages of large volatility and weak stability, which can easily lead to mismatch between the power generation side and the power consumption side, seriously threatening the safety and stability of the power system. To improve the power system's ability to absorb clean energy, energy storage technology is indispensable. However, traditional lithium-ion battery energy storage systems have frequent safety accidents, causing serious economic losses. In addition, lithium batteries are severely limited by resources and their costs are rising.
[0003] Zinc-nickel batteries are secondary batteries with Ni(OH)2 and NiOOH as positive electrodes, ZnO and Zn as negative electrodes, and ZnO-saturated KOH aqueous solution as electrolyte. They have the advantages of high specific energy, high specific power, high operating voltage, good low-temperature performance, convenient application, no memory effect, etc. At the same time, zinc is used as the negative electrode material of the battery, which is low in price and easy to mass produce. Therefore, zinc-nickel batteries are particularly suitable for large-scale energy storage needs supporting wind and solar power generation in the three northern regions. However, the current cycle performance of zinc-nickel batteries is restricted by the problem of dendrite growth at the zinc negative electrode. In alkaline electrolytes, the presence of dendrites will detach from the electrode during the generation process, causing a decrease in capacity. At the same time, the growth of dendrites may damage the diaphragm and cause the battery to short-circuit.
[0004] In order to improve the cycle stability of the negative electrode of zinc-nickel battery, the zinc negative electrode can be modified to be porous. Chinese patent (publication number CN114759168A) discloses the use of a melt casting method to prepare a multi-element zinc-based alloy ingot, and a chemical dealloying method to prepare a nanoporous zinc-based alloy integrated negative electrode and perform heat treatment. By in-situ loading zinc on a nanoporous metal matrix, the zinc dendrites and side reactions on the surface of the zinc negative electrode are solved. However, the zinc negative electrode prepared by this method uses zinc metal, which has high reaction activity. At the same time, the metal casting and chemical dealloying processes require high temperature treatment or chemical treatment, high energy consumption, and certain safety risks. Chinese patent (publication number CN107681129A) provides a three-dimensional zinc / carbon composite material for zinc-based batteries, which is composed of a three-dimensional multi-level carbon conductive network and zinc and / or zinc oxide loaded thereon. However, the carbon skeleton in the porous composite material prepared by this method is relatively fragile, and it is easy to collapse during the charge and discharge process, which ultimately affects the cycle performance. The 3D printing method used at the same time is not suitable for large-scale rapid production. Therefore, it is necessary to develop a new method for preparing ZnO-Zn composite porous bulk negative electrode materials with high cycle performance. Summary of the invention
[0005] In view of the above problems, the present invention discloses a method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery, comprising the following steps:
[0006] The precursor, the phase separation agent, and the solvent are fully stirred at room temperature until they are completely dissolved, and the stirring is continued to obtain a precursor solution;
[0007] Adding a gel accelerator to the precursor solution until the pH of the system is 7, stirring, and removing bubbles by ultrasound to obtain a gel solution;
[0008] The gel solution is sealed and gelled at 50-80° C. and aged for 18-36 hours, then the remaining solvent is poured out, and ethanol is used for washing for multiple times to obtain a porous block of zinc hydroxide;
[0009] Heat treating the zinc hydroxide porous block in vacuum or atmosphere to obtain a ZnO-Zn composite porous block negative electrode material;
[0010] Among them, the mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 10:1 to 5:1.
[0011] Furthermore, the precursor is an inorganic salt of zinc, including any one of zinc chloride, zinc sulfate or zinc nitrate.
[0012] Furthermore, the zinc ion concentration in the precursor solution is 0.1-0.2 mol / L.
[0013] Furthermore, the phase separation agent is one of polyacrylic acid, polyethylene oxide, polyvinyl pyrrolidone, and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer;
[0014] The ratio of zinc ions to phase separation agent in the precursor solution is 1 mol: 0.5-2.0 kg.
[0015] Furthermore, the solvent is a mixed solvent of water and an organic solvent;
[0016] Wherein, the organic solvent is one of propylene glycol, ethylene glycol, ethanol and isopropanol.
[0017] Furthermore, the volume ratio of water to organic solvent is 1:1 to 1:10.
[0018] Furthermore, the gel accelerator is one of propylene oxide, urea, ethanolamine, diethylamine, hexylamine and hexadecylamine.
[0019] Furthermore, the atmosphere is an inert atmosphere or a reducing atmosphere;
[0020] The inert atmosphere is nitrogen or argon; the reducing atmosphere is one of carbon monoxide, methane, ethylene and acetylene.
[0021] Furthermore, the heat treatment temperature is 200-800° C. and the time is 1-5 hours.
[0022] The invention also discloses a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery, wherein the mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 10:1 to 5:1.
[0023] Compared with the prior art, the embodiments of the present invention have at least the following advantages:
[0024] 1. The porous block of zinc hydroxide is prepared by sol-gel phase separation method and a ZnO-Zn composite porous block is formed after heat treatment. The porous structure can effectively alleviate the growth of Zn dendrites and improve the negative electrode cycle performance;
[0025] 2. Carbonization of organic matter during heat treatment can effectively improve the conductivity of ZnO-Zn composite porous blocks, alleviate the problem of decreased electrode conductivity after metal zinc is oxidized to form zinc oxide, and increased battery internal resistance leading to decreased electrochemical performance;
[0026] 3. The zinc formed by reduction is evenly distributed and micro-nano distributed, which further inhibits the formation of dendrites.
[0027] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A flow chart of a method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Figure 1 The flowchart of the method for preparing the ZnO-Zn composite porous block for the negative electrode of the zinc-nickel battery according to the embodiment of the present invention is shown. Figure 1 As shown, the present invention proposes a method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery, comprising the following steps:
[0032] The precursor, phase separation agent, and solvent are fully stirred at room temperature until they are completely dissolved, and the stirring is continued for 2 h to obtain a precursor solution;
[0033] Adding a gelling agent to the precursor solution until the pH of the system is 7, stirring for 5 minutes, and removing bubbles by ultrasonication for 30 seconds to obtain a gel solution;
[0034] The gel solution is sealed and gelled at 50-80° C. and aged for 18-36 hours, and then the remaining solvent is poured out, and washed with ethanol for multiple times to obtain a porous zinc hydroxide block; preferably, the gel is gelled at 60° C. and aged for 24 hours;
[0035] Heat treating the zinc hydroxide porous block in vacuum or atmosphere to obtain a ZnO-Zn composite porous block negative electrode material;
[0036] Among them, the mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 10:1 to 5:1.
[0037] The present invention adopts a sol-gel phase separation method to prepare a zinc hydroxide porous block and forms a ZnO-Zn composite porous block after heat treatment. The porous structure can effectively alleviate the growth of Zn dendrites and improve the negative electrode cycle performance.
[0038] In some embodiments, the precursor is an inorganic salt of zinc, including any one of zinc chloride, zinc sulfate or zinc nitrate. Using an inorganic zinc salt as a precursor has the advantages of low cost and high safety.
[0039] In some embodiments, the zinc ion concentration in the precursor solution is 0.1-0.2 mol / L.
[0040] When the zinc ion concentration in the precursor solution is too low, it is difficult to form a block. When the concentration is too high, the block is dense and has a non-porous structure. When the zinc ion concentration is 0.1-0.2 mol / L, a porous block can be formed.
[0041] In some embodiments, the phase separation agent is one of polyacrylic acid, polyethylene oxide, polyvinyl pyrrolidone, and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer;
[0042] The ratio of zinc ions to phase separation agent in the precursor solution is 1 mol: 0.5-2.0 kg.
[0043] A porous block can only be formed with an appropriate proportion of the phase separation agent. Too much or too little will result in the inability to form a porous block structure.
[0044] In some embodiments, the solvent is a mixed solvent of water and an organic solvent;
[0045] Wherein, the organic solvent is one of propylene glycol, ethylene glycol, ethanol and isopropanol.
[0046] In some embodiments, the volume ratio of water to organic solvent is 1:1 to 1:10. The solvent adopts an appropriate alcohol-water ratio to form a co-continuous skeleton structure.
[0047] In some embodiments, the gel accelerator is one of propylene oxide, urea, ethanolamine, diethylamine, hexylamine, and hexadecylamine. Adding the gel accelerator to the precursor solution can gelate and ensure the formation of a co-continuous skeleton structure of the porous block.
[0048] In some embodiments, the atmosphere is an inert atmosphere or a reducing atmosphere;
[0049] The inert atmosphere is nitrogen or argon; the reducing atmosphere is one of carbon monoxide, methane, ethylene and acetylene.
[0050] In some embodiments, the heat treatment is performed at a temperature of 200 to 800° C. for a time of 1 to 5 hours.
[0051] Heat treatment under the above conditions in an inert or reducing atmosphere can reduce ZnO to Zn, inhibit dendrites and increase the life of the negative electrode material.
[0052] Heat treating the porous zinc hydroxide block in a vacuum or atmosphere according to the above conditions can carbonize the organic matter, which can effectively improve the conductivity of the ZnO-Zn composite porous block and alleviate the problem of reduced electrode conductivity after metal zinc is oxidized to form zinc oxide and increased battery internal resistance leading to decreased electrochemical performance.
[0053] The present invention also discloses a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery prepared by the above-mentioned preparation method of the ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery, wherein the mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 10:1 to 5:1.
[0054] Example 1
[0055] A method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery comprises the following steps:
[0056] 1) Using zinc chloride as a precursor, 35 wt% polyacrylic acid aqueous solution as a phase separation agent, water and glycerol as solvents, stirring them fully at room temperature until they are completely dissolved, and continuing to stir for 2 hours to obtain a precursor solution, wherein the zinc ion concentration is 0.15 mol / L, the amount of 35 wt% polyacrylic acid is 0.8 kg per mol of zinc ion (calculated as an effective ingredient), and the volume ratio of water to glycerol is 1:1 (water includes water in polyacrylic acid and additional solvent);
[0057] 2) Adding gelling accelerator propylene oxide to the precursor solution until the pH of the system is 7, stirring for 5 minutes, and then ultrasonicating for 30 seconds to remove bubbles to obtain a gel solution;
[0058] 3) The gel solution was sealed and gelled at 60° C. and aged for 24 h, and then the remaining solvent was poured out and washed with ethanol for 3 times to obtain a porous block of zinc hydroxide;
[0059] 4) The porous zinc hydroxide block is subjected to vacuum heat treatment at a temperature of 500° C. for 2 h to obtain a ZnO-Zn composite porous block negative electrode material.
[0060] The mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 6:1.
[0061] The prepared ZnO-Zn composite porous block was used as the negative electrode, Ni(OH)2 and NiOOH were used as the positive electrode, and a ZnO-saturated 6 mol / L KOH aqueous solution was used as the electrolyte to assemble a button-type zinc-nickel battery. The capacity retention rate was 80% after 400 cycles at 2C.
[0062] Example 2
[0063] A method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery comprises the following steps:
[0064] 1) Using zinc sulfate as a precursor, polyethylene oxide (molecular weight 1000000) as a phase separation agent, water and glycerol as solvents, stirring them fully at room temperature until they are completely dissolved, and continuing to stir for 2 hours to obtain a precursor solution, wherein the zinc ion concentration is 0.1 mol / L, the amount of polyethylene oxide is 0.5 kg per mol of zinc ion, and the volume ratio of water to glycerol is 1:5;
[0065] 2) adding urea as a gel promoter to the precursor solution until the pH of the system is 7, stirring for 5 minutes, and then ultrasonicating for 30 seconds to remove bubbles to obtain a gel solution;
[0066] 3) The gel solution was sealed and gelled at 60° C. and aged for 24 h, and then the remaining solvent was poured out and washed with ethanol for 3 times to obtain a porous block of zinc hydroxide;
[0067] 4) The porous zinc hydroxide block was heat treated in an argon atmosphere at a temperature of 400° C. for 4 hours to obtain a ZnO-Zn composite porous block negative electrode material.
[0068] The mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 8:1.
[0069] The prepared ZnO-Zn composite porous block was used as the negative electrode, Ni(OH)2 and NiOOH were used as the positive electrode, and a ZnO-saturated 6 mol / L KOH aqueous solution was used as the electrolyte to assemble a button-type zinc-nickel battery. The capacity retention rate was 78% after 400 cycles at 2C.
[0070] Example 3
[0071] A method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery comprises the following steps:
[0072] 1) Using zinc nitrate as a precursor, polyvinyl pyrrolidone (K30) as a phase separation agent, water and glycerol as solvents, stirring them fully at room temperature until they are completely dissolved, and continuing to stir for 2 hours to obtain a precursor solution, wherein the zinc ion concentration is 0.2 mol / L, the amount of polyvinyl pyrrolidone is 2 kg per mol of zinc ion, and the ratio of water to glycerol is 1:10;
[0073] 2) adding urea as a gel promoter to the precursor solution until the pH of the system is 7, stirring for 5 minutes, and then ultrasonicating for 30 seconds to remove bubbles to obtain a gel solution;
[0074] 3) The gel solution was sealed and gelled at 60° C. and aged for 24 h, and then the remaining solvent was poured out and washed with ethanol for 3 times to obtain a porous block of zinc hydroxide;
[0075] 4) The porous zinc hydroxide block was heat treated in a reducing methane atmosphere at a temperature of 300° C. for 3 h to obtain a ZnO-Zn composite porous block negative electrode material.
[0076] The mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 5:1.
[0077] The prepared ZnO-Zn composite porous block was used as the negative electrode, Ni(OH)2 and NiOOH were used as the positive electrode, and a ZnO-saturated 6 mol / L KOH aqueous solution was used as the electrolyte to assemble a button-type zinc-nickel battery. The capacity retention rate was 81% after 400 cycles at 2C.
[0078] Comparative Example 1
[0079] In step 1) of Example 1, no phase separation agent 35 wt % polyacrylic acid aqueous solution was added, and the rest was the same as Example 1.
[0080] Unable to form porous blocks.
[0081] Comparative Example 2
[0082] In step 1) of Example 1, the amount of the phase separation agent 35 wt % polyacrylic acid aqueous solution used is 2.5 kg (calculated as effective ingredient) per mol of zinc ion, and the rest is the same as Example 1.
[0083] Flocculent deposits are formed in the precursor solution, and porous blocks cannot be formed subsequently. The deposits are dried and heat-treated and used as the negative electrode. Button-type zinc-nickel batteries are assembled with Ni(OH)2 and NiOOH as the positive electrode and a 6 mol / L KOH aqueous solution saturated with ZnO as the electrolyte. The capacity retention rate is 25% after 400 cycles at 2C.
[0084] Comparative Example 3
[0085] In step 1) of Example 1, the zinc ion concentration is 1 mol / L, and the rest is the same as Example 1.
[0086] It is impossible to form a porous block, and only a dense ZnO-Zn block can be obtained. A button-type zinc-nickel battery was assembled with Ni(OH)2 and NiOOH as the positive electrode and a 6 mol / L KOH aqueous solution saturated with ZnO as the electrolyte. The capacity retention rate was 20% after 400 cycles at 2C.
[0087] Comparative Example 4
[0088] In step 2) of Example 1, no gelling accelerator propylene oxide was added, and the rest was the same as Example 1.
[0089] Unable to form porous blocks.
[0090] Comparative Example 5
[0091] In step 4) of Example 1, the heat treatment is carried out in air atmosphere, and the rest is the same as Example 1.
[0092] The porous block structure collapsed and the product was zinc oxide. A button-type zinc-nickel battery was assembled with Ni(OH)2 and NiOOH as the positive electrode and a 6 mol / L KOH aqueous solution saturated with ZnO as the electrolyte. The capacity retention rate was less than 10% after 400 cycles at 2C.
[0093] It should be understood that "one embodiment" or "an embodiment" mentioned throughout the specification means that specific features, structures or characteristics related to the embodiment are included in at least one embodiment of the present disclosure. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification does not necessarily refer to the same embodiment. In addition, these specific features, structures or characteristics can be combined in one or more embodiments in any suitable manner. It should be understood that in the various embodiments of the present disclosure, the size of the serial number of the above-mentioned processes does not mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present disclosure. The serial numbers of the embodiments of the present disclosure are for description only and do not represent the advantages and disadvantages of the embodiments.
[0094] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery, characterized in that: The following steps are involved: The precursor, the phase separation agent, and the solvent are fully stirred at room temperature until they are completely dissolved, and the stirring is continued to obtain a precursor solution; Adding a gel accelerator to the precursor solution until the pH of the system is 7, stirring, and removing bubbles by ultrasound to obtain a gel solution; The gel solution is sealed and gelled at 50-80° C. and aged for 18-36 hours, then the remaining solvent is poured out, and ethanol is used for washing for multiple times to obtain a porous block of zinc hydroxide; Heat treating the zinc hydroxide porous block in vacuum or atmosphere to obtain a ZnO-Zn composite porous block negative electrode material; Among them, the mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 10:1 to 5:
1.
2. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 1, characterized in that: The precursor is an inorganic salt of zinc, including any one of zinc chloride, zinc sulfate or zinc nitrate.
3. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 1 or 2, characterized in that: The zinc ion concentration in the precursor solution is 0.1-0.2 mol / L.
4. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 1, characterized in that: The phase separation agent is one of polyacrylic acid, polyethylene oxide, polyvinyl pyrrolidone, and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer; The ratio of zinc ions to phase separation agent in the precursor solution is 1 mol: 0.5-2.0 kg.
5. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 1, characterized in that: The solvent is a mixed solvent of water and an organic solvent; Wherein, the organic solvent is one of propylene glycol, ethylene glycol, ethanol and isopropanol.
6. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 5, characterized in that: The volume ratio of the water to the organic solvent is 1:1 to 1:
10.
7. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 1, characterized in that: The gel accelerator is one of propylene oxide, urea, ethanolamine, diethylamine, hexylamine and hexadecylamine.
8. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 1, characterized in that: The atmosphere is an inert atmosphere or a reducing atmosphere; The inert atmosphere is nitrogen or argon; the reducing atmosphere is one of carbon monoxide, methane, ethylene and acetylene.
9. The method for preparing a ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery according to claim 1, characterized in that: The heat treatment temperature is 200-800° C. and the time is 1-5 hours.
10. A ZnO-Zn composite porous block for a negative electrode of a zinc-nickel battery, characterized in that: The mass ratio of ZnO to Zn in the ZnO-Zn composite porous block is 10:1 to 5:1.
Citation Information
Patent Citations
Three-dimensional zinc / carbon composite material for zinc-based battery and preparation method of three-dimensional zinc / carbon composite material
CN107681129A
Co-doped nano-porous zinc-based alloy integrated negative electrode and preparation method thereof
CN114759168A